2019
DOI: 10.1186/s12974-019-1421-8
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α/STAT3 pathway epigenetically upregulates Nav1.6 expression in DRG and contributes to neuropathic pain induced by L5-VRT

Abstract: BackgroundStudies showed that upregulation of Nav1.6 increased the neuronal excitability and participated in neuropathic pain in the dorsal root ganglion (DRG). However, the molecular mechanisms underlying Nav1.6 upregulation were not reported yet.MethodsThe paw withdrawal threshold was measured in the rodents following lumbar 5 ventral root transection (L5-VRT). Then qPCR, western blotting, immunoprecipitation, immunohistochemistry, and chromatin immunoprecipitation assays were performed to explore the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…Apparently, the double-labeled immunofluorescence results were not in line with the prevailing view but were still consistent with some other former studies. 55,56 Similarly, the enhanced IL-1b expression was detected on the neurons of BCP rats, aggravating inflammation of spinal dorsal horn. We must admit that a large number of studies showed that astroglia or microglia secreted IL-1b activated neurons through IL-1R during inflammation or neuropathic pain.…”
Section: Discussionmentioning
confidence: 95%
“…Apparently, the double-labeled immunofluorescence results were not in line with the prevailing view but were still consistent with some other former studies. 55,56 Similarly, the enhanced IL-1b expression was detected on the neurons of BCP rats, aggravating inflammation of spinal dorsal horn. We must admit that a large number of studies showed that astroglia or microglia secreted IL-1b activated neurons through IL-1R during inflammation or neuropathic pain.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, an altered DNA methylation pattern has been demonstrated in neurodegenerative diseases, such as AD and PD [ 26 ], which are typically characterized by neuroinflammation and a predominant presence of TNFα cytokine. Interestingly, DNA methylation changes and other epigenetic mechanisms underlying TNFα-mediated effects have been reported in a number of cell types [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Overall, these findings suggest the importance of analyzing epigenetic actions of TNFα in human neuronal models.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, activated p38 can also directly regulate the phosphorylation of the Nav1.8 channel and increase the level of TRPV1 in the DRG neurons [61,63]. Furthermore, proinflammatory cytokines upregulate the expression of Nav1.7 and Nav1.6, which contributes to peripheral sensitization and neuropathic pain [64,65]. Therefore, the activation of TLR8 may increase the neuronal excitability of TG neurons via regulating the expression and function of sodium channel.…”
Section: Tlr8 Is Involved In the Increase Of Intracellular Calcium Anmentioning
confidence: 99%